Esensi Komitmen Terhadap Nilai-Nilai Kebangsaan - Aulia, Novira; Albina, Meyniar (Media Hukum Indonesia (MHI), 2025)
This study aims to examine the essence of commitment to national values in order to strengthen national identity and unity amidst the challenges of globalization and cultural diversity. National values, such as love of the homeland, unity, justice, and mutual cooperation, are important foundations in building a strong and competitive nation. Using a qualitative approach, this study explores how commitment to national values can be instilled through education, policies, and daily life practices. The results of the study indicate that strengthening national values requires collaboration between families, schools, communities, and the government. Instilling these values is not only able to face the threat of disintegration, but also forms a generation with character.